The practical engineer [IC design, power reduction]. - Frenkil, J.
The need of popular portable electronics for long battery life is placing power reduction at the top of every IC design engineer's to-do list. A new breed of design automation tools is helping them scrimp on power at every step of the VLSI design process. The automation tools can be differentiated, to a first order, by the level of abstraction on which they operate. Lowest of all are the transistor level tools. These possess the best accuracy, but commensurately require the longest run times and have the smallest capacities-the size of the circuit that can be analyzed. While transistor level tools can assist with analyses earlier in the design process, they are typically used to characterize cells and modules for use at the higher abstraction levels. The next level of abstraction embraces the logic-level power analysis tools. The highest abstraction level for which power analysis tools exist today is the architectural level. This type of tool analyzes abstract design representations such as Verilog or VHDL RTL code. The use of these tools in power reduction design is outlined
Keywords: IC design; VHDL RTL code; VLSI design process; Verilog; Architectural level; Design automation tools; Logic-level power analysis tools; Long battery life; Low-power IC design; Portable electronics; Power reduction; Transistor level tools